2016
DOI: 10.21608/ejnf.2016.74975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Niacin and/or Thiamin Supplementations on Growth and Fattening Performance of Buffalo Calves.

Abstract: his study was conducted to evaluate the effect of feeding supplemented diets by ether niacin, thiamin or its mixture on the growth and fattening performance of buffalo calves. A feeding trial was carried out using twenty growing buffalo calves with average initial weight 275±2.6 Kg and aged 14 months. They were divided into four similar groups (5 calves each) in 120-day feeding trial periods using the randomized complete block design. All animals' groups were fed individually along the experimental period on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
3
1
0
Order By: Relevance
“…The current findings are in line with previous studies on the influence of Cr-Met, niacin, and added to the ruminant rations on the serum TP and their fractions [50,39,54]. Moreover, the niacin and Cr-Met groups had significantly lower serum urea and creatinine levels than the other groups, but there was a significant difference between the niacin and Cr-Met groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current findings are in line with previous studies on the influence of Cr-Met, niacin, and added to the ruminant rations on the serum TP and their fractions [50,39,54]. Moreover, the niacin and Cr-Met groups had significantly lower serum urea and creatinine levels than the other groups, but there was a significant difference between the niacin and Cr-Met groups.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to those by Deka et al [36], who reported that chromium adding to lactating buffaloe rations improved nutrient digestibility, but didn't affected on it with growing cattle [37]. The findings of nutritive values are similar to those obtained by Kraidees et al [38], Abou-Elenin et al [39] and Ghoniem et al [40], when Cr-yeast, niacin, or yeast were added to the ruminant ration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Chemical composition of ingredients and calculated experimental rations fed to calves during the restricted and re-alimentation periods are presented in Table ( 1). These data revealed that the chemical composition of concentrate feed mixture (CFM), corn silage (CS), berseem hay (BH), ammoniated rice straw (TRS) and calculated composition of experimental rations are within the normal ranges published by Mostafa et al (2015), Abou Elenin et al (2016), Ghoniem, et al (2017) and Abdou (2018). Also, data in Table 1 showed that DM, OM, CP, EE and NFE contents decreased and CF and ash contents increased with decreasing the levels of concentrate mixture in all restricted rations (T2, T3 and T4) than that of control ration (T1, unrestricted ration).…”
Section: Chemical Composition Of Ingredients and Rationssupporting
confidence: 66%
“…For example, according to Bryant et al [ 9 ] and Baldin et al [ 10 ], the supplementation of fat-soluble vitamins alone (A) or associated (D and E) did not influence animal performance and carcass traits of finishing bulls. On the other hand, some studies have demonstrated better productive performance of bulls [ 11 ] and buffaloes [ 12 ] in response to water-soluble vitamin supplementation (vitamins B1 and B3).…”
Section: Introductionmentioning
confidence: 99%